Leadership Styles and Innovation Capital towards SMEs Performance Sustainability - Hazlina HASSAN; Shukriah SAAD; Amrizah KAMALUDDIN; Nurhayati AB SAMAD (Communications of International Proceedings, 2020)
To date, numerous studies have been conducted regarding Small and Medium Enterprises (SMEs) performance and sustainability. It is notable that in the global business competitiveness, SMEs are facing various challenges in surviving and sustaining their operations. Thus, SMEs need to exploit all of their available resources including good leadership styles and innovative initiatives to ensure the sustainability of organization’s growth. The current study aims at identifying the relationship between leadership style and innovation capital towards the SMEs sustainability.  It is always a major academic issue in determining whether a successful leader share similar experiences, attributes and leadership patterns. A good leadership styles can reshape and redefine the direction of SMEs performance. This paper describes the pattern of self-perception of leadership styles among SMEs top management team. Data were collected from 111 SMEs. The results from this study indicate that all leadership styles; directing, coaching, facilitating and delegating have significant relationships on sustainable competitive advantage of SMEs. The Delegating approach shows the highest score as it is indicating that good leadership should be able to delegate responsibilities to others. The results also show that innovation capital is significantly positive towards the sustainability of SMEs performance. This would be the main strategy for leaders in strategizing the appropriate leadership approaches which concentrate on innovation capital as key capabilities of the organization to achieve sustainable competitive advantage. This is very important for the SMEs not only to withstand the competition and strive, but to continue improving their performance with a dynamic market in Malaysia.
Keywords: Leadership styles; Innovation Capital; SMEs and Sustainability.